Instructional Cueing Alters Upper Limb Muscle Activity and Kinematics During Elastic Resistance Exercise. (December 2021) - Reece, Ashley A.; Parkinson, James E.; Cudlip, Alan C.; Page, Phil; Holmes, Michael W.R.
Abstract : Objective: The purpose of this study was to quantify the differences in upper limb muscle activity and kinematics when performing shoulder elastic resistance exercises with no cue, slouched posture, and corrected posture. Design: Fifteen healthy participants completed four shoulder elastic resistance exercises (unilateral flexion, bilateral flexion, external rotation, and external rotation with towel) across three simulated body postures (no cue, corrected posture, and slouched posture). Surface electromyography was measured on 16 upper limb muscles and kinematics were collected. Two-way repeated-measures analyses of variance examined differences in muscle activation and kinematics across postures and exercises. Results: Interactions between exercise and posture were found for most muscles. Muscle activity interactions existed in 14 of the 16 muscles examined, with 8 muscles having the greatest activity in the unilateral flexion, slouched condition ( P < 0.0001). The slouched posture generated activity up to 88.4 ± 5.1 %MVC in the cervical extensors. Completing flexion or external rotation exercises with a slouched posture led to increased glenohumeral range of motion ( P < 0.0001), but these differences were less than 5 degrees between the greatest and smallest ranges of motion (85.8 vs. 81.0 degrees). Conclusion: Posture influenced muscle activation and kinematics, with slouched postures increasing muscle activity and range of motion. There was little to no difference between the no cue and corrected cue conditions, suggesting that perhaps a clinician's time may be better spent focusing on avoiding slouched postures rather than ensuring mastering technique.